The influence of social media marketing and official websites on the decision to use offline travel agents through service quality at the Ray Fish Fast Cruises company - Suardana, Ida Bagus Raka; Putri, Ni Kadek Amanda Maharani (EDUCTUM: Journal Research, 2026)
Advances in digital technology have revolutionized communication patterns and relationships between companies and their consumers, including in the tourism industry. Social media and official websites are now used by companies such as Ray Fish Fast Cruises to provide service information, promote products, and attract consumer interest. This study was conducted to analyze the influence of Social Media Marketing and Official Websites on Offline Travel Agent Usage Decisions through Service Quality. The results indicate that Social Media Marketing does not have a significant influence on Service Quality (p-value 0.775), while Official Websites have a positive and significant influence on Service Quality (p-value 0.000). Service Quality has a positive and significant impact on Usage Decisions (p-value 0.000). Social Media Marketing has a significant positive influence on Usage Decisions (p-value 0.000), while Official Websites have no significant influence on Usage Decisions (p-value 0.996).